Effect of BAP and 2,4-D Combination on the Callus Induction of Robusta Coffee (Coffea canephora Pierre ex A.Froehner) Leaf Explants - Yovita Angeline Wijaya; Ratih Restiani; Aniek Prasetyaningsih (Universitas Labuhanbatu, 2025)
Background: Sustainable production of Robusta coffee (Coffea canephora) is constrained by the limited availability of high-quality planting materials, while information regarding the optimal auxin–cytokinin combinations for initiating callus cultures remains insufficient. Accordingly, this study was conducted to examine the effects of combined applications of benzyl amino purine (BAP) and 2,4-dichlorophenoxyacetic acid (2,4-D) on callus induction and subsequent growth derived from young leaf explants of Robusta coffee. Methodology: Explant cultures were established on Murashige and Skoog (MS) medium enriched with different concentrations of 2,4-D (1, 1.5, and 2 ppm) in combination with BAP (1.5, 2, and 2.5 ppm), arranged in a completely randomized design with three replications. Data collection was conducted throughout a 30-day incubation period and included measurements of callus initiation time (days), callus formation percentage, callus growth intensity, and callus morphological features. The resulting data were analyzed statistically using analysis of variance (ANOVA), followed by the Kruskal–Wallis test. Findings: Result describe that the treatment combining 2,4-D at 1 ppm with BAP at 1.5 ppm produced the most favorable response, as indicated by the shortest callus initiation period (7.33 DAP). In contrast, the application of 2,4-D at 1 ppm in combination with BAP at 2.5 ppm achieved a 100% callus induction rate and the highest callus growth intensity (2 on a 5-point scale), along with a compact callus exhibiting a yellowish-green coloration. Overall, these results highlight the critical influence of auxin–cytokinin equilibrium in enhancing callus induction in Robusta coffee and underscore its significance as a foundational reference for establishing an efficient in vitro propagation strategy. Contribution: In general, this study contributes to providing important technical information supporting the large-scale and sustainable production of high-quality Robusta coffee seedlings